PENGEMBANGAN MEDIA PEMBELAJARAN POP-UP BOOK SUB BAHASAN MANUSIA PURBA DI INDONESIA - Puspitasari, Ita; Noor, Agus Sastrawan; Chalimi, Ika Rahmatika (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractPresent study aim to develop a pop-up book learning media sub-discussion of early humans in Indonesia in class X. Early human sub-discussion in Indonesia is material that studi abstract objects for students so that students find it difficult to understand ancient human material in Indonesia. Moreover, in conveying of material, the references are using still lacked in the form of several historical package books and several LKS. The research method used was the 4-D model development (R & D). However, researchers were only research only up to the third D. Present results showing validity and practicality in the material aspects of 81.6% with good criteria and revised as needed. Students responses to the pop-up book media carry out on a small scale of 12 people and a large scale of 25 consecutive people who receive a percentage of 79.2% (with strong criteria) and 85.7% (with very strong criteria). Based on the measurement of media effectiveness based on the results of the assessment of the pretest and posttest in the form of multiple choice questions with the number of 30 items obtaine n-gain 0.6 with moderate information. Keywords: Pop-Up Book?s Media, Sub-Discussion of Early Humans in Indonesia